(untitled) (Research, Society and Development, 2023)
The objective of this work is to investigate what are the contributions of the practice of psychologists who work in hospitals from the national literature; as well as describing the work process of psychologists according to the discussions carried out by articles at the national level in the last five years and reflecting from the discussions in the literature about the potentialities and challenges inherent to the work performed by psychologists in hospitals. The present work is configured as a Literature Review - RL with an Integrative approach. With regard to the data collection stage, it took place through virtual consultations in the following databases: Periodicals Electronics in Psychology (PePSIC) and Scientific Electronic Library Online (SciELO). The searches were carried out in November 2022, using descriptors and/or keywords. Finally, Content Analysis was used in the analysis stage of the publications selected for this work. The results express little development of scientific articles on the subject in question, mainly in the northeast and north of the country, in addition to the selected articles that fit the inclusion criteria, it was possible to observe the contributions of the professional performance of the category of psychology in maternity hospitals, Intensive Care service, the importance of welcoming and psychological care with stomized patients.